Systematic Literature Review: Analisis Faktor Risiko Diabetes Melitus Tipe 1 pada Anak dan Remaja di Negara Maju Wilayah Eropa Barat - Dwi Ambarwati Nur Ammatullah (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
The incidence of type 1 diabetes mellitus mostly occurs in children and adolescents has increased significantly every year, especially in developed countries in Western Europe which continue to experience the highest increase. The purpose of this study was to analyze the risk factors for type 1 diabetes in children and adolescents in developed countries in Western Europe. This type of research is a systematic literature review. The literature search strategy as a source of information was carried out by accessing electronic databases online, namely Science Direct, PubMed, and Google Scholar. Article quality assessment using Critical Appraisal Skill Programme (CASP). The results showed that out of 10 (2014-2024), conducted in the United Kingdom (n=1), Sweden (n=1), Germany (n=1), England (n=2), Denmark (n=3), Norway (n=1) and conducted in Norway and Denmark (n=1). Of the 10 articles, 5 out of 10 articles examined BMI on the development of type 1 diabetes in children and adolescents. The results of this systematic review found that age, gender, race, family history of diabetes, socioeconomic, BMI, nutritional intake in mothers and children, physical activity, infection and smoking will increase the risk of type 1 diabetes mellitus in children and adolescents in developed countries in Western Europe.